The truth about Twinkie Pie - Yeh, Kat (Little, Brown and Company, 2015)
"When twelve-year-old GiGi and her big sister DiDi move to Long Island from South Carolina for GiGi to attend a fancy new private school, GiGi has a new recipe for success and makes new friends, but then discovers a family secret that turns her life upside-down"--